Human G protein-coupled receptor 30 is N-glycosylated and N-terminal domain asparagine 44 is required for receptor structure and activity. Issue 2 (26th February 2019) - Gonzalez de Valdivia, Ernesto; Sandén, Caroline; Kahn, Robin; Olde, Björn; Leeb-Lundberg, L.M. Fredrik
Abstract : G protein-coupled receptor 30 (GPR30), or G protein-coupled estrogen receptor (GPER), is a G protein-coupled receptor (GPCR) that is currently attracting considerable attention in breast cancer and cardiometabolic regulation. The receptor was reported to be a novel membrane estrogen receptor mediating rapid non-genomic responses. However, questions remain about both the cognate ligand and the subcellular localization of receptor activity. Here, we used human embryonic kidney (HEK) 293 (HEK293) cells ectopically expressing N-terminally FLAG-tagged human GPR30 and three unique antibodies (Ab) specifically targetting the receptor N-terminal domain (N-domain) to investigate the role of N -glycosylation in receptor maturation and activity, the latter assayed by constitutive receptor-stimulated extracellular-regulated protein kinase (ERK) 1/2 (ERK1/2) activity. GPR30 expression was complex with receptor species spanning from approximately 40 kDa to higher molecular masses and localized in the endoplasmatic reticulum (ER), the plasma membrane (PM), and endocytic vesicles. The receptor contains three conserved asparagines, Asn 25, Asn 32, and Asn 44, in consensus N -glycosylation motifs, all in the N-domain, and PNGase F treatment showed that at least one of them is N -glycosylated. Mutating Asn 44 to isoleucine inactivated the receptor, yielding a unique receptor species at approximately 20 kDa that was recognized by Ab only in a denatured state. On the other hand, mutating Asn 25 or Asn 32 either individually or in combination, or truncating successively N-domain residues 1–42, had no significant effect either on receptor structure, maturation, or activity. Thus, Asn 44 in the GPR30 N-domain is required for receptor structure and activity, whereas N-domain residues 1–42, including specifically Asn 25 and Asn 32, do not play any major structural or functional role(s).